Penapisan Dan Pencegahan Hiperkolesterolemia di Desa Mukti Sari, Kecamatan Tapung, Kampar - Ariza Julia Paulina; Fatmawati; Chandra Wijaya; Meimi Laila; Tiara Yulia Rahmi; Fadli Maggribi (LPPM UMRI, 2025)
Cholesterol sufferers in Indonesia are quite high, reaching 28%, that 7.9% of them die due to hypercholesterolemia. Hypercholesterolemia can lead to the risk of atherosclerosis, coronary heart disease (CHD), pancreatitis, diabetes mellitus, liver disease, thyroid disorders and kidney disease. In 2020, CHD was the main cause of death, around 36% of all deaths. Risk factors for hypercholesterolemia include genetics, consumption of high-fat foods, lack of exercise and smoking habits. The aim of this activity is to improve the knowledge of the people of Mukti Sari Village, Tapung District, Kampar Regency, Riau Province about hypercholesterolemia and detect hypercholesterolemia so that it can be managed further. The activity stages consist of: participants were given questions before and after education activities about hypercholesterolemia. Check blood cholesterol levels using the Family Dr. cholesterol checker. Service activities in the form of counseling succeeded in increasing the knowledge of the people of Mukti Sari Village, Tapung District, Kampar Regency about hypercholesterolemia. There are 3% of the people of Mukti Sari Village who experience hypercholesterolemia. Keywords: Coronary Heart Disease (CHD), Hypercholesterolemia, Kampar, Mukti Sari Village